Kaluza Klein Type FRW Cosmological Model With Extended Chaplygin Gas. Issue 2 (3rd July 2019) - Khadekar, G. S.; Ramtekkar, N. A.
Abstract: In this paper we consider the extended Chaplygin gas equation of state as a model of dark energy for which it recovers barotropic fluids with quadratic equation of state. We obtain scale factor dependence energy density and Hubble expansion parameter for particular values of n, m and α . Similarly for arbitrary values of n, m and α we have discuss nature of cosmological parameters such as scale factor, Hubble expansion parameter, time dependent dark energy density and deceleration parameter in the framework of Kaluza Klein type FRW cosmological model. Further, we study stability of the model by using speed of sound and observe that the model is stable at late time.